PENGARUH MODEL PEMBELAJARAN PBLTERINTEGRASI ICT TERHADAP MODEL MENTAL DAN SELF EFFICACY PESERTA DIDIK PADA PEMBELAJARAN IPA - Rahmi Hanifah; Yanti Fitria (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the effect of Problem Based Learning (PBL) integrated with Information and Communication Technology (ICT) on students' mental models and self-efficacy in elementary school science learning. This study used a quantitative approach with a quasi-experimental nonequivalent control group design. The study population consisted of fourth-grade students in Cluster I, Pariaman Tengah District, in the 2024/2025 academic year, with two classes selected through purposive sampling as the experimental and control groups. Data were collected using a validated mental model test and self-efficacy questionnaire, then analyzed using descriptive and inferential statistics, including prerequisite tests and independent sample t-tests. The results showed that the experimental class obtained a higher mental model post-test score (79.17) than the control class (59.17). Self-efficacy scores increased significantly in the experimental group from 50.54 to 81.08, while the control group only reached 63.75. The results of statistical tests showed a significant difference between groups (p < 0.05). These findings indicate that ICT-integrated PBL is effective in improving students' conceptual understanding and self-confidence, thus becoming a relevant and innovative learning strategy to improve the quality of science learning in elementary schools.